Exostosin1 as a novel prognostic and predictive biomarker for squamous cell lung carcinoma: A study based on bioinformatics analysis. (13th December 2020) - Wu, Disheng; Huo, Chao; Jiang, Siyu; Huang, Yanxia; Fang, Xuehong; Liu, Jun; Yang, Min; Ren, Jianwei; Xu, Bilian; Liu, Yi
Abstract: The exostosin (EXT) protein family is involved in diverse human diseases. However, the expression and prognostic value of EXT genes in human lung squamous cell carcinoma (LUSC) is not well understood. In this study, we analyzed the association between expression of EXT1 and EXT2 genes and survival in patients with LUSC using bioinformatics resources such as Oncomine and The Cancer Genome Atlas (TCGA) databases, the Gene Expression Profiling Interactive Analysis (GEPIA) server and Kaplan–Meier plotter. Furthermore, regulatory microRNAs (miRNAs) were predicted for EXT1 and used to establish a potential miRNA‐messenger RNA (mRNA) regulation network for LUSC using the ENCORI platform. We observed that EXT1 and EXT2 expression levels were higher in LUSC than those in normal tissues. However, only EXT1 expression was significantly associated with poor overall survival (OS) in LUSC patients. Functional annotation enrichment analysis showed that genes co‐expressed with the EXT1 gene were enriched in biological processes such as cell adhesion and migration, and KEGG pathways such as extracellular matrix receptor interactions, complement and coagulation cascades, and cell death. Furthermore, three miRNAs, hsa‐mir‐190a‐5p, hsa‐mir‐195‐5p, and hsa‐mir‐490‐3p, were identified to be potentially involved in the regulation of EXT1 . In summary, we identified EXT1 expression as a novel potential prognostic marker for human LUSC and the regulatory miRNAs that could possibly contribute to the prognosis of the disease. Abstract : EXT1 expression as a novel potential prognostic marker for human lung squamous cell carcinoma and the regulatory miRNAs that could possibly contribute to the prognosis of the disease.